A Geospatial Bibliometric Review of the HIV/AIDS Epidemic in the Russian Federation - Gray Neils, Megan E.; Pfaeffle, Herman O. I.; Kulatti, Art T.; Titova, Alena; Lyles, Galina S.; Plotnikova, Yulia; Zorkaltseva, Elena; Ogarkov, Oleg B.; Vitko, Serhiy M.; Dillingham, Rebecca A.; Heysell, Scott K. (Frontiers in Public Health, 2020)
Background: Increasing rates of HIV/AIDS in Eastern Europe and Central Asia contrast global trends, but the scope of HIV/AIDS research originating from RF and countries of the former Soviet Union (FSU) has not been quantified or comparatively examined. Methods: We searched six major scientific databases in Russian and English languages with medical subject heading terms “HIV” or “AIDS” and “Russia” or “Soviet Union” from 1991 to 2016. Each abstract indexed was reviewed and tagged for 25 HIV/AIDS research themes, location of research focus and first author. Results and discussion: A total of 2868 articles were included; 2156 (75·1%) and 712 (24·8%) described research in RF and FSU respectively. There were 15 publications per million population in RF. Federal districts of RF with the highest rates of HIV had the most limited publications. An interactive web-map with time-lapse features and links to primary literature was created using ArcGIS® technology [http://arcg.is/2FUIJ5v]. Conclusion: We found a lower than expected publication rate in RF relative to rising HIV prevalence. The greatest deficits were in the most HIV burdened regions in RF. Our findings highlight opportunities for new research strategies and public health efforts among key populations and subnational regions.